Comparative transcriptome and metabolite survey reveal key pathways involved in the control of the chilling injury disorder superficial scald in two apple cultivars, ‘Granny Smith’ and ‘Ladina’ - Vittani, Lorenzo; Populin, Francesca; Stuerz, Stefan; Buehlmann, Andreas; Khomenko, Iuliia; Biasioli, Franco; Bühlmann-Schütz, Simone; Vrhovsek, Urska; Masuero, Domenico; Zanella, Angelo; Busatto, Nicola; Costa, Fabrizio (Frontiers in Plant Science, 2023)
The low temperature normally applied to prevent fruit decay during the storage of apples, can also triggers the onset of a chilling injury disorder known as superficial scald. In this work, the etiology of this disorder and the mechanism of action of two preventing strategies, such as the application of 1-MCP (1-methylcyclopropene) and storage at low oxygen concentration in ‘Granny Smith’ and ‘Ladina’ apple cultivars were investigated. The metabolite assessment highlighted a reorganization of specific secondary metabolites, in particular flavan-3-ols and unsaturated fatty acids, while the genome-wide transcriptomic analysis grouped the DEGs into four functional clusters. The KEGG pathway, GO enrichment analysis, together with the gene-metabolite interactome, showed that the treatment with 1-MCP prevented the development of superficial scald by actively promoting the production of unsaturated fatty acids, especially in ‘Granny Smith’. ‘Ladina’, more susceptible to superficial scald and less responsive to the preventing strategies, was instead characterized by a higher accumulation of very long chain fatty acids (VLCFAs). Storage at low oxygen concentration stimulated a higher accumulation of ethanol and acetaldehyde together with the expression of genes involved in anaerobic respiration, such as malate, alcohol dehydrogenase and pyruvate decarboxylase in both cultivars. Low oxygen concentration, likewise 1-MCP, through a direct control on ethylene prevented the onset of superficial scald repressing the expression of PPO, a gene encoding for the polyphenol oxidase enzyme responsible of the oxidation of chlorogenic acid. Moreover, in ‘Granny Smith’ apple, the expression of three members of the VII subgroups of ERF genes, encoding for elements coordinating the acclimation process to hypoxia in plants was observed. The global RNA-Seq pattern also elucidated a specific transcriptomic signature between the two cultivars, disclosing the effect of the different genetic background in the control of this disorder.